THE DEPLOYMENT OF SOVIET CHEMICAL FORCES IN AFGHANISTAN AND SOUTHEAST ASIA - Meyer, C.M.; Theron, P. (Scientia Militaria - South African Journal of Military Studies, 2012)
’And let there be no doubt: if hostilities should break out, the Soviet Army would use chemical weapons against its opponents.’ Col Oleg Penkovsky Recently chemical warfare has become a most distinct feature of military technique. This can be said after it has been established that the Soviet Union used chemical agents in South-East Asia and Afghanistan. The first reports dealt with some unexplained deaths among the Hmong people of Laos and shortly afterwards came the discovery of tiny yellow deposits of pollen containing lethal toxins. In the wake of this discovery the United States alleged that Soviet-backed forces were using ’yellow rain’ toxins in violation of treaties banning biological and chemical weapons. The Soviets’ strong denial met with skepticism in Western circles, and did nothing to quell a raging debate over the precise interpretation of toxins found in Kampuchea and Afghanistan. In this overview the facts and reports pertaining to the topic under discussion are correlated and examined..